2015
DOI: 10.1039/c5ra20022a
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of multilayer films of graphene oxide/copper phthalocyanine with high dielectric properties

Abstract: Novel multilayer films of graphene oxide/copper phthalocyanine (GO/CuPc) were fabricated by self-assembling in the orientational ordered liquid crystalline state and immobilizing of the ordered structure upon casting and drying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…The three-dimensional (3D) layer-by-layer multilayer films of GO/ CuPc composites with a thickness of ∼0.1 mm were successfully fabricated by self-assembling in the orientation liquid crystalline state as a precursor and immobilizing the ordered structure upon simple casting and drying as reported by our previous work. 17 A compact layer-by-layer configuration can be confirmed by scanning electron microscopy (SEM) as shown in Figure 1a and b. To prepare highly fluffy ordered layer-by-layer nitrogen-doped graphene multilayer films, indispensable thermal annealing for achieving the effective reduction of GO nanosheets and pyrolysis of nitrogen-enriched CuPc molecules were employed at high temperature.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The three-dimensional (3D) layer-by-layer multilayer films of GO/ CuPc composites with a thickness of ∼0.1 mm were successfully fabricated by self-assembling in the orientation liquid crystalline state as a precursor and immobilizing the ordered structure upon simple casting and drying as reported by our previous work. 17 A compact layer-by-layer configuration can be confirmed by scanning electron microscopy (SEM) as shown in Figure 1a and b. To prepare highly fluffy ordered layer-by-layer nitrogen-doped graphene multilayer films, indispensable thermal annealing for achieving the effective reduction of GO nanosheets and pyrolysis of nitrogen-enriched CuPc molecules were employed at high temperature.…”
Section: Resultsmentioning
confidence: 91%
“…Multilayer films of graphene oxide/copper phthalocyanine were prepared as reported. 17 The homogeneous liquid crystal dispersions of GO/CuPc (100 mg of GO and 50 mg of CuPc) in NMP were cast on a clean preheated glass of quartz plate (30 mm × 30 mm), and the solvent was evaporated using a sequential mode of temperature programmed at 80, 100, 120, 140, 160, 180, and 200 °C for 2 h, respectively. The obtained layer-by-layer GO/CuPc multilayer films (labeled as GO/CuPc) loaded on the quartz plate were annealed at a higher temperature of 800 °C for 3, 6, and 9 h under the nitrogen atmosphere, which can be marked as NG-3h, NG-6h, and NG-9h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Graphene shows a wide range of applications: composite materials, , catalysis, energy, electromagnetic protection, etc. Macroscopic paper-like graphene sheets with exceptional mechanical properties and electrical conductivity have received significant attention, which is expected to be used in the fields of aerospace and flexible electronics, , such as supercapacitors, , nanogenerators, water treatment, lithium ion batteries, , sensors, and electromagnetic wave shielding. , However, the mechanical properties of two-dimensional graphene materials are poor due to the weak mutual bonding force, which limits their application. Therefore, enhancing the properties of paper-like graphene sheets is particularly important, which is mainly solved by optimizing the assembly of graphene sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Most Pc derivatives are susceptible to energy or electron transfer processes due to the presence of π‐electron conjugated ring system and consequently exhibit exceptionally high dielectric constant with an order corresponding to 10 4 , which finds useful as a dielectric filler for dielectric composites. Recently, Pc‐grafted CNTs have been reported to exhibit outstanding dielectric properties as conductive fillers for composites, in which Pc were decorated with either amino or hyper branched substituents with respect to their approaches …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pc-grafted CNTs have been reported to exhibit outstanding dielectric properties as conductive fillers for composites, in which Pc were decorated with either amino or hyper branched substituents with respect to their approaches. [20][21][22][23][24][25][26] There have previously reported that the solubility and compatibility of Pcs are effectively modulated when solubilityenhancing substituents were introduced into the peripheral of a Pc ring as a result of reduced intermolecular aggregation effect. [27][28][29][30][31] Herein, following this line of thought, we present the synthesis and applications of alkylated and perfluorinated Pc derivatives for covalent functionalization of CNTs, in order to further address such critical requirements for dispersion and adhesive properties of CNTs inside the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%